Hopfield Neural Networks with Unbounded Monotone Activation Functions. (31st December 2012) - Tatar, Nasser-eddine
Abstract : For the Hopfield Neural Network problem we consider unbounded monotone nondecreasing activation functions. We prove convergence to zero in an exponential manner provided that we start with sufficiently small initial data.